2020
DOI: 10.1021/acs.oprd.0c00091
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Electrochemical Batch Reactor for Synthetic Organic and Inorganic Transformations and Analytical Electrochemistry

Abstract: A standardized and versatile electrochemical batch reactor that has wide applicability in both organic and inorganic synthesis and analytical electrochemistry has been developed. A variety of synthetic electrochemical transformations have been performed to showcase the versatility and demonstrate the reactor, including the synthesis of five Cu(I)-NHC, two Au(I)-NHC and one Fe(II)-NHC complex, as well as an Fe(III)-salen complex. The reactor is based on a commercially available vial with an adapted lid, making … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Current developments in the field of synthetic electrochemistry will allow more chemists access to electrochemical methods. As such, tutorials [1 ° ,1p] and the advancement of new, user‐friendly equipment [2d,53] will catalyze the adoption of electrochemistry as an everyday method in the synthetic laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current developments in the field of synthetic electrochemistry will allow more chemists access to electrochemical methods. As such, tutorials [1 ° ,1p] and the advancement of new, user‐friendly equipment [2d,53] will catalyze the adoption of electrochemistry as an everyday method in the synthetic laboratory.…”
Section: Discussionmentioning
confidence: 99%
“… Selected examples of metal‐NHC complexes synthesized electrochemically by A : Chen and co‐workers; [38] B : Willans and co‐workers; [2d,39] C : Abbehausen and co‐workers [40] …”
Section: Electrochemical Synthesis Of Nhcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, based on the electrochemical method, it is possible to choose appropriate NHC precursors [43]. A number of electrochemical studies related to the NHC metal complexes were also reported [44][45][46][47][48], the data of few selective NHC precursors (i.e., azolium salts) and its corresponding reduction potential are summarized from the literature (Table 2).…”
Section: Arrangement Of Imidazolium Salts Based On Their Pk a Values ...mentioning
confidence: 99%
“…To determine if 2.2 F mol −1 is necessary in the electrolysis step to achieve full conversion to benzaldehyde in the catalytic step, the electrolysis was performed as above with aliquots taken at time intervals corresponding to a range of 1.0−2.3 F mol −1 (Figure 1). 48 The catalytic step requires a basic reaction medium, and any residual triflic acid from the electrolysis step may neutralize the N-methylimidazole present in the catalytic step. The sensitivity of the catalytic reaction was probed by spiking the reaction mixture with triflic acid, and the efficiency of the reaction was found to be highly susceptible to the presence of triflic acid (Table S2).…”
mentioning
confidence: 99%